Penerapan Sistem Full Day School Dalam Rangka Peningkatan Kualitas Pendidikan Di MI Al-Qamar Bagor, Nganjuk - Addin Arsyadana (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
Efforts to improve the quality of education in essence not only lead to the results of education, but also on the process of implementation of education, the process here including the applied curriculum model. With regard to the application of curriculum, full day school system is one form of educational model that is considered to improve the quality of education. In this study, we want to find out whether the full day School system can improve the quality of education, the factors that can be the obstacles and supporters of the implementation, and how far the full day school system can improve the quality of education. Research that the authors do is included in the study with a qualitative approach. By data collecting method writer use observation method, interview, questionnaire and documentation.